The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1094/phyto.2003.93.7.891
|View full text |Cite
|
Sign up to set email alerts
|

Field Resistance to Strobilurin (QoI) Fungicides in Pyricularia grisea Caused by Mutations in the Mitochondrial Cytochrome b Gene

Abstract: Gray leaf spot caused by Pyricularia grisea is a highly destructive disease of perennial ryegrass turf. Control of gray leaf spot is dependent on the use of preventative fungicide treatments. Strobilurin-based (Q(o)I) fungicides, which inhibit the cytochrome bc(1) respiratory complex, have proven to be very effective against gray leaf spot. However, in August 2000, disease was diagnosed in Q(o)I-treated perennial ryegrass turf on golf courses in Lexington, KY, Champaign, IL, and Bloomington, IL. To determine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
147
2
10

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(164 citation statements)
references
References 19 publications
5
147
2
10
Order By: Relevance
“…1) binds with a hydrogen bond to the amide group of glutamic acid at position 272 in domain C; therefore, this region plays an important role in accepting fungicides. Since substitution of glycine for alanine at position 143 (G143A) in domain B significantly lowers the affinity of strobilurin fungicides to cytochrome b, 7,8,13,14,[19][20][21][22][23] interaction between domain B and strobilurin fungicides must be strong. On the other hand, substitution of phenylalanine for leucine at position 129 (F129L) in domain A has been shown not to significantly lower the affinity of strobilurin fungicides to cytochrome b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) binds with a hydrogen bond to the amide group of glutamic acid at position 272 in domain C; therefore, this region plays an important role in accepting fungicides. Since substitution of glycine for alanine at position 143 (G143A) in domain B significantly lowers the affinity of strobilurin fungicides to cytochrome b, 7,8,13,14,[19][20][21][22][23] interaction between domain B and strobilurin fungicides must be strong. On the other hand, substitution of phenylalanine for leucine at position 129 (F129L) in domain A has been shown not to significantly lower the affinity of strobilurin fungicides to cytochrome b.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, substitution of phenylalanine for leucine at position 129 (F129L) in domain A has been shown not to significantly lower the affinity of strobilurin fungicides to cytochrome b. 14,21) This suggests that interaction between domain A and strobilurin fungicides might be rather weak. The result obtained here that strobilurin fungicides inhibited SCR activities of crops, rats and carp rather potently, which have different amino acid residues from those of fungi at position 130 in domain A (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations mediating a G143A-or a F129L exchange lead to complete loss or drastic reduction of fungicide efficacies (26,31). Single spore isolates of the apple powdery mildew Podosphaera leucotricha collected from commercial orchards were all heteroplasmic with respect to their mitochondrial cytochrome b gene and differed in strobilurin sensitivity.…”
Section: Qualitative and Quantitative Fungicide Resistancementioning
confidence: 99%
“…33,34) The mutation at codon 129 (TTC→ TTA) is associated with moderate resistance, and mutation at codon 143 (GGT→ GCT) is associated with resistance. 34) In Taiwan, rice blast is endemic to the first rice cultivation (March to June), affecting over 20,000 ha each year. 35) Previous studies showed the presence of more than 20 races of M. oryzae by the standard lines of rice.…”
Section: Introductionmentioning
confidence: 99%